2018
DOI: 10.1002/hep.30037
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic‐Associated Disruption of Microbiota Composition and Function in Cirrhosis Is Restored by Fecal Transplant

Abstract: In patients with advanced cirrhosis on lactulose and rifaximin, FMT restored antibiotic-associated disruption in microbial diversity and function. (Hepatology 2018; 00:000-000).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
93
1
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 109 publications
(98 citation statements)
references
References 45 publications
(107 reference statements)
2
93
1
2
Order By: Relevance
“…This was paralleled by a decrease of systemic endotoxin levels [30]. Further metabolomics changes as consequence of rifaximin in patients with cirrhosis include a reduction in secondary/primary bile acid ratios and other indicators of microbiota metabolic function [27,31].…”
Section: Discussionmentioning
confidence: 95%
“…This was paralleled by a decrease of systemic endotoxin levels [30]. Further metabolomics changes as consequence of rifaximin in patients with cirrhosis include a reduction in secondary/primary bile acid ratios and other indicators of microbiota metabolic function [27,31].…”
Section: Discussionmentioning
confidence: 95%
“…FMT was effective for these patients via inducing HBeAg clearance, suggesting that regulating intestinal microbiota might be beneficial to chronic hepatitis B treatment. A Phase I clinical trial demonstrated that FMT restored antibiotic‐induced microbial dysbiosis in patients with advanced liver cirrhosis . Even more, the effect of FMT on hepatic encephalopathy has been confirmed in both animal models and human beings.…”
Section: Fmt As a Possible Therapy For Various Type Of Cancers And Camentioning
confidence: 99%
“…secondary BAs increased and primary reduced, to baseline levels. Secondly, SCFAs that fell pre FMT were restored partly post FMT and lastly, the predicted functionality related to xenobiotic and lipid metabolism were higher after antibiotics, whereas bioenergetics, BA, Amino acids, glycans and vitamin/cofactor metabolism were higher post FMT 74 . Another phase 1 trial involving FMT via oral capsules in recurrent OHE has been completed ( NCT03152188) .…”
Section: Future Conceptsmentioning
confidence: 95%